A 17,000-Year-Long Record of Vegetation and Fire from Cradle Mountain National Park, Tasmania - Stahle, Laura N.; Whitlock, Cathy; Haberle, Simon G. (Frontiers in Ecology and Evolution, 2016)
On centennial to millennial timescales fire regimes are driven by climate changes, vegetation composition and human activities. We reconstructed the postglacial vegetation and fire history based on pollen and charcoal data from a small lake in Cradle Mountain National Park and investigated the influence that climate, people, and vegetation had on past fire regimes. In the late-glacial period, a slowly warming climate led to a shift in vegetation from coniferous alpine shrubland to Phyllocladus woodland. During this period, fire activity was very low. The initial increase in fires occurred between 12,500–11,000 cal yr BP and led to a decline in forest taxa, a resurgence of grasses and a rise in the pyrophytic buttongrass Gymnoschoenus. The highest fire activity in the record occurred between 10,900–9400 cal yr BP, the warmest interval of the postglacial period based on independent proxy records. Subalpine trees had depressed levels of pollen during this time. After 9000 cal yr BP, fire activity declined substantially, and fire-sensitive rainforest reached its maximum extent ca. 8500–6500 cal yr BP. A major fire perturbation occurred ca. 3,600 cal yr BP, and thereafter rainforest shifted to open Eucalyptus woodland. The comparison of reconstructed fire and vegetation history at Wombat Pool to climate records and archeological data indicated that climate was the primary driver of the observed changes. In the late glacial and early Holocene, climate warming and individual species dispersal traits likely drove changes in vegetation composition that in turn impacted the fire regime. A relatively wet mid-Holocene climate favored rainforest trees whereas the drier and more variable climate of the late Holocene contributed to a decline in rainforest and a shift toward mixed forest as wet sclerophyll elements increased. Archeological evidence suggests humans reoccupied the region ca. 4000 cal yr BP. This may have added an ignition source that was absent in the previous ca. 7000 years and may have contributed to the large fire event ca. 3600 cal yr BP. Although pre-European populations may have been a source of ignition locally, the reconstructed fire history trends from Cradle Mountain National Park match well with large-scale changes in climate patterns.